Suicide prevention plans and suicide mortality in Spain, 2010-2023: an interrupted time-series analysis - Flórez, Gerardo; Espandian, Ashkan; Seoane-Pillado, Teresa; Gerpe, José Manuel; Villa, Rocío; Serrano-García, Antonio; Saiz, Pilar (Frontiers in Psychiatry, 2025)
BackgroundThe serious problem posed by suicide deaths has led to increased awareness and the implementation of prevention plans in a large number of countries worldwide. The main aim of this study is to determine the relationship between the variation in completed suicide rates in Spain and its autonomous communities from 2010 to 2023, and the implementation of suicide prevention strategies at an autonomous community level.MethodsThe incidence rates of suicide deaths in the nineteen Spanish autonomous communities from 2010 to 2023 were obtained from the Spanish Statistical Office. Suicide prevention strategies were classified using the Universal–Selective-Indicated model, with strategies including interventions at all three levels considered multilevel. An interrupted time series analysis was conducted to evaluate the impact of suicide prevention programs on suicide rates. The fitted model included the pre-intervention trend, the immediate change after implementation, and the change in slope from that point onward. Suicide rates at the national level and in Murcia, where no prevention plan was implemented, were included as control variables.ResultsNone of the tested interrupted time series analysis variants showed a significant reduction in the rate of completed suicides in any autonomous community. The only exceptions were the first year of implementation of the prevention plan in Galicia and Madrid after adjusting for the national rate and using Murcia as the control region for the after-intervention analysis.ConclusionDespite the suicide prevention plans launched by numerous Spanish autonomous communities, to date no significant reduction in the evolution of completed suicide rates has been demonstrated in any of these autonomous communities or nationwide.